1990
DOI: 10.1152/ajpgi.1990.258.2.g216
|View full text |Cite
|
Sign up to set email alerts
|

Human intestinal water absorption: direct vs. indirect measurements

Abstract: Distilled water, a carbohydrate-electrolyte (CE; 4% sucrose, 2% glucose, 17.2 meq/l NaCl, and 2.8 meq/l KCl) solution, or a 10% glucose solution, all containing the nonabsorbed indicator polyethylene glycol (PEG) and deuterium oxide (D2O, 30 ppm), were infused (15 ml/min) into the duodenojejunum of seven men by using the triple lumen technique. Net water absorption was determined directly from the change in PEG concentration and was calculated from plasma D2O derived from D2O in the perfusion solutions. The pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
51
4

Year Published

1999
1999
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(55 citation statements)
references
References 9 publications
0
51
4
Order By: Relevance
“…In contrast to the results of Gisolfi et al (1990) andRehrer et al (1992), there are data to show that there is good agreement between the results of perfusion studies and those obtained with the deuterium tracer method. Leiper et al (1988a) have reported that the rate of deuterium accumulation was about 50% faster after ingestion of a dilute carbohydrateelectrolyte solution than after ingestion of plain water: this same solution was shown to slightly slow the rate of gastric emptying (Leiper et al 1988b) but to promote an increase in the rate of intestinal water uptake (Leiper & Maughan, 1986).…”
Section: Methodscontrasting
confidence: 79%
See 4 more Smart Citations
“…In contrast to the results of Gisolfi et al (1990) andRehrer et al (1992), there are data to show that there is good agreement between the results of perfusion studies and those obtained with the deuterium tracer method. Leiper et al (1988a) have reported that the rate of deuterium accumulation was about 50% faster after ingestion of a dilute carbohydrateelectrolyte solution than after ingestion of plain water: this same solution was shown to slightly slow the rate of gastric emptying (Leiper et al 1988b) but to promote an increase in the rate of intestinal water uptake (Leiper & Maughan, 1986).…”
Section: Methodscontrasting
confidence: 79%
“…In spite of the evidence to show that the tracer accumulation method produces results that are in broad agreement with predictions made on the basis of the known gastric emptying and intestinal water absorption characteristics of the test drinks compared, doubts have been raised as to the usefulness of this technique (Gisolfi et al 1990). In the study of Gisolfi et al (1990), the net rate of water flux in a segment of the small intestine was measured using a triple lumen perfusion method while three different solutions were perfused at a fixed rate; the test solutions were distilled water, a 6% carbohydrate-electrolyte solution and a 10% glucose solution.…”
Section: Methodsmentioning
confidence: 91%
See 3 more Smart Citations